New approach to agro-industrial solid and liquid waste management: Performance of an EGSB reactor at different hydraulic retention times for methane production - Rodrigues, Caroline Varella (2024)
This study investigated the removal of agro-industrial wastes (5 g COD L⁻1 from coffee and 0.5 g COD L⁻1 from brewery wastewater, plus 1 g L⁻1 of coffee pulp and husk) in a continuous Expanded Granular Sludge Bed (EGSB) reactor at 35 °C. The effect of Hydraulic Retention Times (HRTs) of 72h, 48h, and 24h on CH₄ yield was examined using a mixed culture of cattle manure and granular sludge. Methane yields were 201, 124.5, and 113.8 mL CH₄ g⁻1 COD for the 1st, 2nd, and 3rd phases, respectively. Volatile fatty acids, particularly acetic acid, increased at lower HRTs. Sequencing of the 16S rRNA gene on the Illumina HiSeq platform revealed a syntrophic relationship between Syntrophorhabdus, Syntrophobacter, and Pseudomonas with methanogens Methanomassiliicoccus, Methanospirillum, and Methanobacterium, aiding in the removal of phenolic compounds. The study suggests that an HRT of 72h is optimal for maximizing CH₄ production in the EGSB reactor.